Analisis Pengaruh Penerapan Safety Driving Monitoring System (SDMS) Berbasis GPS terhadap Kinerja Operasi Melalui Peran Mediasi Kinerja Keselamatan Pengemudi Truk - Muhammad Hidjrah Sultansyah; Adithya Sudiarno (Journal of Management and Social Sciences, 2026)
The high contribution of human factors to truck fleet accidents has encouraged PT XYZ to implement a GPS-based Safety Driving Monitoring System (SDMS) as an effort to improve driving safety and operational performance. This study aims to analyze the effects of SDMS completeness and reliability, feedback and coaching, and managerial integration on SDMS usage intensity, as well as to examine the effect of SDMS usage intensity on driver safety performance and operational performance through the mediating role of driver safety performance. This study employed an explanatory quantitative approach involving 170 tronton truck drivers as respondents selected using a probability sampling method. Data analysis was conducted using Covariance-Based Structural Equation Modeling (CB-SEM) to examine the relationships among research variables. The results indicate that SDMS completeness and reliability, feedback and coaching, and managerial integration positively influence SDMS usage intensity. Furthermore, SDMS usage intensity significantly improves driver safety performance and operational performance, while driver safety performance strengthens the relationship between SDMS usage and operational performance. This study implies that the successful implementation of SDMS is not only determined by technological aspects but also by managerial support and user behavior management in improving fleet safety and operational efficiency.